Calculează, respectând regulile învățate.
a.52 + (64 - 25:5) x 2
b. 309-3x (100 - 72:9)
c. 84 - 120: (90 x 2:10 - 6)
d. (99 + 3) x 21 x 0:7
e. 104: 2 + (6 + 36:6) x 5
f. 4 + 4 x (4 + 4 x 4) - 36:9:2
g. (5 + 5 x 3) x 3 - (3 x 25 + 24): 3
h. (25+25) x 3 - (25 + 25 x 3): 5
i. 400 - 2 x 10 + (650 + 310): 3
1.8 +3 x (12:4+ 21:7:3)
j. 10 + 10:(10 10 - 10 x 9)
k. 127 + (36: 9 - 1) x 8:2
nu vreau doar rezultatele
Răspunsuri la întrebare
Explicație pas cu pas:
a. 52+(64-25÷5)×2=52+(64-5)×2
=52+59×2
=52+118
=170
b. 309-3×(100-72÷9)=309-3×(100-8)
=309-3×92
=309-276
=33
c. 84-120÷(90×2÷10-6)=84-120÷(180÷10-6)
=84-120÷(18-6)
=84-120÷12
=84-12
=72
d. (99+3)×21×0÷7=102×21×0÷7
=2142×0÷7
=0÷7
=0
e. 104÷2+(6+36÷6)×5=104÷2+(6+6)×5
=52+12×5
=52+60
=112
f. 4+4×(4+4×4)-36÷9÷2=4+4×(4+16)-4÷2
=4+4×20-2
=4+80-2
=84-2
=82
g. (5+5×3)×3-(3×25+24)÷3=(5+15)×3-(75+24)÷3
=20×3-99÷3
=60-33
=27
h. (25+25)×3-(25+25×3)÷5=50×3-(25+75)÷5
=150-100÷5
=150-20
=130
i. 400-2×10+(650+310)÷3=400-20+960÷3
=380+320
=700
1.8+3×(12÷4+21÷7÷3)=8+3×(3+3÷3)
=8+3×(3+1)
=8+3×4
=8+12
=20
j. 10+10÷(10×10-10×9)=10+10÷(10×10-90)
=10+10÷(100-90)
=10+10÷10
=10+1
=11
k. 127+(36÷9-1)×8÷2=127+(4-1)×8÷2
=127+3×8÷2
=127+24÷2
=127+12
=139